2019
DOI: 10.1080/0284186x.2019.1615637
|View full text |Cite
|
Sign up to set email alerts
|

NordScreen – an interactive tool for presenting cervical cancer screening indicators in the Nordic countries

Abstract: Introduction: Quality assurance and improvement of cancer screening programs require up-to-date monitoring systems and evidence-based indicators. National quality reports exist but the definition and calculation of indicators vary making comparisons between countries difficult. The aim is to stimulate collaborative research and quality improvements in screening through freely available, comparable and regularly updated quality indicators. The project currently includes data on cervical cancer screening but pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…Furthermore, we have identified a number of indicators that can be used in a population based on structure, process, and outcome of cancer indicators according to the Donabedian’s model [ 27 ]. Studies have concluded that a comparison of outcomes is challenging at the national and international levels because of the non-parametric nature of the indicators [ 11 , 12 , 20 , 22 , 23 , 24 ]. Our assessment of indicators showed that the structure of cancer care is not a high priority in the healthcare system of Korea, which is already well established.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we have identified a number of indicators that can be used in a population based on structure, process, and outcome of cancer indicators according to the Donabedian’s model [ 27 ]. Studies have concluded that a comparison of outcomes is challenging at the national and international levels because of the non-parametric nature of the indicators [ 11 , 12 , 20 , 22 , 23 , 24 ]. Our assessment of indicators showed that the structure of cancer care is not a high priority in the healthcare system of Korea, which is already well established.…”
Section: Discussionmentioning
confidence: 99%
“…To date, development of indicators related to cancer management, have focused one of the following, national cancer screenings or early detection [ 11 , 12 ], diagnosis [ 13 , 14 ], treatment [ 14 ], quality of care [ 15 , 16 , 17 , 18 ], survivor management [ 19 , 20 ], and end-of-life care [ 21 ]. Although there has been much work involved in the development of indicators related to the quality or performance of specific types of cancer [ 16 , 17 , 18 , 19 , 20 , 21 ], minimal attention has been paid to the lifecycle of cancer or cancer care continuum.…”
Section: Introductionmentioning
confidence: 99%
“…Only some of the Nordic countries adhere to the recommendation to include time and place for screening in the invitation. This strategy for increasing coverage should be incorporated to all programmes since none of the countries yet reach the desirable test coverage level of 85% [31] defined in the EU guidelines [8]. Removing the out-of-pocket costs of screening in Iceland and Norway could also help in increasing the coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Nordscreen is a much welcomed initiative to collect and present data on cervical screening activities in the Nordic countries. The database and the interactive webpage are described in this issue of Acta Oncologica [1]. The Nordic countries have much in common in these areas: Tax-funded health-care systems; organized cervical screening since at least two decades; a common commitment to public health with governments' responsibility for the prevention of disease, equally for the entire population; and the personal number system, decisive for effective population-based screening and for monitoring and improving quality by linkage of data.…”
Section: Nordic Cervical Screening On Common Groundmentioning
confidence: 99%